Multi-lingual multi-platform investigations of online trade in jaguar parts. - John Polisar; Charlotte Davies; Thais Morcatty; Mariana Da Silva; Song Zhang; Kurt Duchez; Julio Madrid; Ana Elisa Lambert; Ana Gallegos; Marcela Delgado; Ha Nguyen; Robert Wallace; et al. (PLoS ONE, 2023)
We conducted research to understand online trade in jaguar parts and develop tools of utility for jaguars and other species. Our research took place to identify potential trade across 31 online platforms in Spanish, Portuguese, English, Dutch, French, Chinese, and Vietnamese. We identified 230 posts from between 2009 and 2019. We screened the images of animal parts shown in search results to verify if from jaguar; 71 posts on 12 different platforms in four languages were accompanied by images identified as definitely jaguar, including a total of 125 jaguar parts (50.7% posts in Spanish, 25.4% Portuguese, 22.5% Chinese and 1.4% French). Search effort varied among languages due to staff availability. Standardizing for effort across languages by dividing number of posts advertising jaguars by search time and number of individual searches completed via term/platform combinations changed the proportions the rankings of posts adjusted for effort were led by Portuguese, Chinese, and Spanish. Teeth were the most common part; 156 posts offered at least 367 teeth and from these, 95 were assessed as definitely jaguar; 71 of which could be linked to a location, with the majority offered for sale from Mexico, China, Bolivia, and Brazil (26.8, 25.4, 16.9, and 12.7% respectively). The second most traded item, skins and derivative items were only identified from Latin America: Brazil (7), followed by Peru (6), Bolivia (3), Mexico (2 and 1 skin piece), and Nicaragua and Venezuela (1 each). Whether by number of posts or pieces, the most commonly parts were: teeth, skins/pieces of skins, heads, and bodies. Our research took place within a longer-term project to assist law enforcement in host countries to better identify potential illegal trade and presents a snapshot of online jaguar trade and methods that also may have utility for many species traded online.